Bocavirus and rotavirus co-infection in children with acute gastroenteritis and associated risk factors - Yaseen Mohammad, Mohammad; Mujahid Al-Shuwaikh, Arwa; Talib Al-Hamdani , Haider (Diyala Journal of Medicine, 2023)
Background: Both Viruses are the leading cause of acute gastroenteritis in infants and young children and are considered an important cause of mortality worldwide. Objective: To estimate the rate of human bocavirus and rotavirus co-infection in children with acute gastroenteritis and determine any association with different risk factors. Patients and Methods: Stool samples were collected from one hundred children suffering from acute gastroenteritis at the Central Teaching Hospital of Pediatrics, Baghdad, Iraq, for the period from December 2021 to April 2022. Samples were stored at -20 °C until they were utilized by PCR and ELISA to identify the human bocavirus (HBoV) DNA and rotavirus antigen (RV-Ag), respectively. Results: This cross-sectional study showed that HBoV DNA was detected in 10 out of 100 samples (10%), while RV-Ag was detected in 22 out of 93 samples (23.66%), and the co-infection rate was 100% (All cases positive for HBoV were also positive for RV). None of the studied demographic data and risk factors showed a significant association with HBoV and/or rotavirus infection (P>0.05). Conclusion: Most NICU deaths resulted from prematurity and respiratory distress syndrome. Enhancing healthcare personnel skills, standardizing protocols, and evidence-based practices for preterm and respiratory distress syndrome management can help reduce neonatal mortality rates in Iraq.